Identification of proboscidean tusk from the Plio-Pleistocene transition of the Pekecik Section, Eastern Turkey - Ranjan, Pranav B.; V. Titov, Vadim; Tesakov, Alexey S.; Trikhunkov, Yaroslav I.; celik, Hasan (Kmk Scientific Press Ltd, Moscow State Univ, 2022)
A fragment of proboscidean tusk from Pekecik (Plio-Pleistocene transition), Turkey, was studied to ascertain its taxonomic identification and biostratigraphic signal. Characteristic properties of the dentine (Schreger structures) were measured along the transversal and longitudinal sections. Schreger angles showed an increasing range from the tusk axis to the cement-dentine junction (CDJ) with values ranging from 61-109 degrees. The variability of the qualitative Schreger pattern from the X type near the tusk axis to the V type at the cement-dentine junction (CDJ), were recorded. The wavelength of dentinal tubules showed a decreasing trend from 1.67 mm near the axis to 1.0 mm near the CDJ. Based on these properties, the specimen was compared with already published data and is tentatively assigned to a meridionaloid elephant cf. Archidiskodon sp. In our research, we conclude that the tusk microstructure features are a practical means of taxonomic study.
Keywords: Quaternary; Pliocene; Proboscidea; tusk; Schreger patterns; Mammuthus; Archidiskodon; CDJ